Lodo de Estação de Tratamento de Água na composição de substratos para produção de mudas de plantas da Caatinga - Augusto, José (2013)
The water treatment process creates a high amount of sludge. Because of that, sludge disposal alternatives should be studied based on technical, economic, environmental, social and political aspects. The present study aimed to evaluate the use of water treatment plant sludge in the composition of substrates for production of seedlings from typical plants of the Caatinga vegetation. Experiments composed of angico, aroiera and sabiá seedling production were carried out at the Experimental Farm of the Federal Institute of Education, Science and Technology of Paraiba (IFPB) - Sousa campus, state of Paraíba, Brazil, between February and May 2015. For each plant species, an experiment using randomized block design was performed. Each experiment consisted of 5 substrates (S1: 70% soil + 30% bovine manure + 0% WTP sludge; S2: 65% soil + 25% bovine manure + 10 % WTP sludge; S3: 60% soil + 20% bovine manure + 20% WTP sludge; S4: 55% soil + 15% bovine manure + 30% WTP sludge and S5: 50% soil + 10% bovine manure + 40% WTP sludge) and 4 repetitions. The evaluated characteristics were: germination (G), stem diameter (SD), shoot height (H), length of the main root (LMR), dry weight of shoot (DWS), dry mass of roots (DMR) total dry matter (TDM), ratio between shoot height and stem diameter (H/SD), ratio between dry weight of shoot and dry mass of roots (DWS/DMR) and Quality Dickson Index (QDI). For the angico seedlings, it was found high values of SD, H, DWS, TDM and H/SD when the substrates 2, 3, 4 and 5 were used. For the other variables, similar results were observed. The aroeira seedlings presented high values of SD when substrates 3, 4 and 5 were used, which is similar to the other studied characteristics. With regard to the sabiá seedlings, there was not substrate influence over the variables. The studied water treatment plant sludge can be used as part of substrates for angico, aroeira and sabiá seedlings production, composing up to 40%.